Microeconomic analyses of the health of the elderly in China - Liu, Lefan (2016)
China is currently facing unprecedented health challenges; non-communicable diseases (NCD) now account for 80 percent of its 10.3 million deaths annually. China’s growing health challenges arise, at least in part, due to its rapidly aging population and are compounded by its inadequate social security provision and rapid urbanization. This dissertation examines the extent to the health and well-being of the elderly in China are affected in the presence of these demographic and social changes. It uses data from a rich but relatively underutilized data source, the China Health and Retirement Longitudinal Study (CHARLS). CHARLS is the first Health and Retirement Study (HRS) of its kind in China, and as such represents a rich source of data on health and well-being for the country. A two-province sample was piloted in 2008 and followed up in 2012, while a national wave was surveyed in 2011. This dissertation is a collection of three self-contained empirical studies on the health and well-being of the elderly in China. The first study examines the effect that chronic diseases have on different dimensions of health in a structural equation framework. The second study examines the extent to which elderly households are able to continue to finance their consumption in the presence of ill-health and the extent to which health insurance and family support from children play a role. In the last study, we further investigate the effect that adult children’s migration decisions have on the physical and subjective well-being of their elderly parents.